Synthesis and Characterization of New Diketone Analogues of Podophyllotoxin - K. H. Hemakumar; A. D. Sathisha; Y. B. Basavaraju (E-Journal of Chemistry)
The new compounds 6,6a-dihydro-2,3-dimethoxy-9-nitro–11bH benzo [C]-fluoren 5,7-dione, 6,6a-dihydro-2,3-dimethoxy-9-chloro–11bH benzo[C]-fluoren-5,7-dione and 6,6a-dihydro-2,3-dimethoxy-9-fluoro–11bH benzo[C]-fluoren-5,7- dione were synthesized in high yields. They are analogues of naturally occurring lignan podophyllotoxin which exhibits anticancer activity. They are very essential to study anticancer activity.